DEVELOPMENT OF NATURAL TOURISM POTENTIAL TNBBS (RESORT BALIK BUKIT CASE STUDY) - Novita Siti Rahayu; Bainah Sari Dewi (University of Lampung, 2023)
ABSTRACT. Ecotourism is a development concept that comes from the tourism industry, can be tainable. The purpose of this research is to determine the potential of ecotourism in Balik Bukit Resort TNBBS, to know the role of managers in the development of natural tourism in Balik Bukit TNBBS Resort, to know the role of the community in the development of ecotourism at Balik Bukit Resort TNBBS, to identify the role of students towards TNBBS. The research location is at Balik Bukit Resort TNBBS in August 2021. The method used in this research is direct observation or direct observation and interviews with keynote speakers or very influential people. The results obtained are the ecotourism potential found at Balik Bukit Resort TNBBS there are three waterfalls, namely a waterfall Sepapah Kiri, a waterfall named Sepapah Kanan and a waterfall named Way Asahan, rivers, Campgrounds, Education Center Kokedama, diversity forest orchid species and landscape ecology. The role of the manager in the management of tourism objects is directly involved in the management, security of visitors, ticket booths and providing facilities. The role of the community in the development of tourism objects helps the manager in providing guide services, services for selling and transportation. The role of students in the National Park is to assist in the development of tourism objects, and research.Keywords: Development.,Ecotourism., Management., Society., Tourism.